Background and temperature effects on Uca panacea color change - Kronstadt, Stephanie M.; Darnell, M. Zachary; Munguia, Pablo (Marine biology, 2013)
Organismal coloration is used for communication, camouflage, and thermoregulation. These functions of body coloration may impose conflicting demands upon color-changing organisms. Here, we examined interacting thermoregulatory and camouflage color change responses when fiddler crabs Uca panacea were subject to simultaneously changing temperatures (10, 25, 40 °C) and backgrounds (black, white). Crab coloration lightened on a white background and at high temperatures and darkened on a black background and at low temperatures, reflecting the camouflage and thermoregulatory functions of color change. Synergistic background and temperature treatments (i.e., hot/white or cold/black) induced strong color change responses. When temperature and background were in conflict (i.e., hot/black or cold/white), responses to background coloration constrained thermoregulatory color change such that carapace coloration did not change. Such conflicts are likely to be common in nature, especially in highly heterogeneous environments. Throughout the experiment, males remained lighter than females and showed a greater response to the hot/white treatment, driven by a stronger response to high temperatures. These differences may reflect the physiological, morphological, and behavioral differences associated with sexual selection and sexual dimorphism in this species.